Keberlanjutan Kegiatan Perikanan Darat Nelayan Skala Kecil Selama Masa Pandemi Covid-19 dan Mendatang (Studi Kasus di Danau Semayang, Kalimantan Timur) - Dina Muthmainnah; K Fatah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Muthmainnah D, Fatah K. 2021. Sustainability of small-scale fisher of inland fishery during the Covid-19 pandemic and in the future (Case Study in Semayang Lake, East Kalimantan). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 114-124. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Inland capture fisheries are characterized by small-scale fisher. Semayang Lake is utilized by fisher, located in Kutai Kartanegara Regency, East Kalimantan. This paper aims to find out the perspective of small-scale fisher regarding the utilization of Semayang Lake during the Covid-19 pandemic and the desired management strategy. Data were collected by interviewing used the questionnaires with closed and open answered to 100 fishers. Respondents are encouraged to express their opinion. The data is presented in graphs and descriptions, and then it is analyzed qualitatively. The results show that all respondents continue to carry out capture fisheries and aquaculture activities during the Covid-19 pandemic. Fishers understand the need to maintain fisheries sustainability. The Covid-19 pandemic has had an impact on declining incomes. The strategy to increase revenue is the need for training on improving the selling value of fish. The role of local governments and fishery extension workers is needed widely to assist the wise use of aquatic resources.